Pengaruh Kualitas Jaringan Provider, Reputasi Perusahaan dan E-Service terhadap Perilaku Perpindahan Merek (Brand Switching) pada Kartu Perdana Telkomsel - Anwar, Saiful; Adi Santoso; Sri Hartono (MAMEN: Jurnal Manajemen, 2022)
The purpose of this study is to determine the effect of Provider Network Quality, Company Reputation and E-Service on Brand Switching. Brand switching itself is done by leaving old products and replacing new products. This research is a quantitative research, multiple linear regression analysis is used in this research. The data in this study uses primary data, namely data obtained based on student Telkomsel card users. The population of this study were students of the Muhammadiyah Ponorogo University management study program class of 2018. The number of respondents who met the criteria was 51 respondents. The instrument in this study used a questionnaire with a Likert scale which had five alternative answers. Validity test is calculated using the product moment formula, while the reliability test uses Croncbach's Alpha formula and hypothesis testing uses multiple linear regression. According to the results of this study, it has a partial positive and significant effect on the Provider Network Quality (X1) and E-Service (X3) variables, while for Company Reputation (X2) it partially produces negative research. as well as all variables by simultaneously producing a significant value. This study produces a correlation coefficient (R) of 0.63 and a coefficienta determination of 0.397. This means that the ability of the independent variables consisting of Provider Network Quality, Company Reputation, and E-Service in explaining the dependent variable Brand Transfer is 39.7% and the remaining 60.3% is influenced by other factors.